2012
DOI: 10.1186/1476-069x-11-16
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale spatial variability of heat-related mortality in Philadelphia County, USA, from 1983-2008: a case-series analysis

Abstract: BackgroundHigh temperature and humidity conditions are associated with short-term elevations in the mortality rate in many United States cities. Previous research has quantified this relationship in an aggregate manner over large metropolitan areas, but within these areas the response may differ based on local-scale variability in climate, population characteristics, and socio-economic factors.MethodsWe compared the mortality response for 48 Zip Code Tabulation Areas (ZCTAs) comprising Philadelphia County, PA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 22 publications
3
102
0
1
Order By: Relevance
“…Heat-related illnesses are associated with a suite of individual, social, and environmental factors that are themselves strongly interrelated (Reid et al 2009;Hondula et al 2012;Harlan et al 2013;Petitti et al 2015). The causal mechanisms leading to heat illnesses and deaths are not fully understood, although research is making progress in explaining linkages between spatial variations in living conditions and individual risks.…”
Section: Connecting Environment With Heat Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Heat-related illnesses are associated with a suite of individual, social, and environmental factors that are themselves strongly interrelated (Reid et al 2009;Hondula et al 2012;Harlan et al 2013;Petitti et al 2015). The causal mechanisms leading to heat illnesses and deaths are not fully understood, although research is making progress in explaining linkages between spatial variations in living conditions and individual risks.…”
Section: Connecting Environment With Heat Vulnerabilitymentioning
confidence: 99%
“…However, extensive scale-dependent variation in LST is expected throughout any given day due to different speeds of warming within the complex spatial structure of urban environments (Li et al 2011;Weng et al 2011). Furthermore, the human consequences of urban LST warming are not well characterized at very fine spatial resolutions, such as individual residential parcels, although several studies have found LST variation affects spatial variability in the risk of heatrelated mortality at neighborhood scales (Johnson et al 2009;Buscail et al 2012;Hondula et al 2012;Johnson et al 2012;Harlan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Specific linkages to human outcomes demonstrate that UHI impacts tend to be registered most highly among those parts of city that have dense occupation with low levels of shade, either from buildings or trees, and greenspaces. These conditions, at least in the U.S. cities examined, tend to be related to lower levels of income, often linked to neighborhoods dominated by certain ethnic groups (Buyantuyev & Wu, 2010;Harlan et al, 2006;Hondula et al, 2012;Jenerette et al, 2007Jenerette et al, , 2011. Finally, the land architecture of urban areas, from the parcel to larger levels of assessment, has been hypothesized to amplify or ameliorate ecosystem services, such as those related to SUHI effects (Turner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Extensively examined, the UHI draws increasing attention owing to its effects on energy and water consumption, human health, environmental (ecosystem) services, especially in the context of global warming (e.g. Gober, Kirkwood, Balling, Ellis, & Deitrick, 2009;Harlan, Brazel, Prashad, Stefanov, & Larsen, 2006;Harlan, Declet-Barreto, Stefanov, & Petitti, 2013;Hondula, Vanos, & Gosling, 2013;Hondula et al, 2012). For these and other reasons, attention to the means to mitigate the UHI effect have garnered considerable attention, especially through model simulations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Microscale urban climate models and remotely sensed data (on the order of 1 m 2 to 1 km 2 ) are often employed for heat stress analysis (e.g., Harlan, Declet-Barreto, Stefanov, & Petitti, 2013;Hondula et al, 2012;Masson, Champeaux, Chauvin, Meriguet, & Lacaze, 2003;Mishra, Ganguly, Nijssen, & Lettenmaier, 2015;Stefanov, Prashad, Eisinger, Brazel, & Harlan, 2004), with airborne remotely sensed data providing surface temperatures at a resolution ranging from 7 to 140 m (Stefanov et al, 2004). These scales may possess insufficient spatial resolution to determine certain personal health impacts based on micro-environmental heat exposure.…”
Section: Introductionmentioning
confidence: 99%